2007
DOI: 10.1007/s10404-007-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and impact of Taq enzyme adsorption on surfaces in microfluidic devices

Abstract: We investigated the adsorption of Taq enzyme, using sessile droplets, on different microfluidic materials. In propagating adsorption materials, the contact angle (CA) of a sessile Taq droplet continually recedes and collapses due to adsorption. Contrastingly, in contained adsorption materials it exhibits an initial reduced CA due to an instantaneous adsorption, however remains timeinvariant. Spectrophotometer analysis on SU8, a propagating adsorption material, reveals a gradual loss of Taq from the droplet ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
0
28
0
2
Order By: Relevance
“…Jeyachandran et al showed that BSA molecules can be adsorbed to both hydrophobic and hydrophilic surfaces [23] with differing adsorption mechanisms and rates [9]. Prakash et al systematically studied polymerase adsorption on 13 materials [11], but this study did not use actual PCR conditions, and thus the results are not necessarily translatable to PCR compatibility due to the temperature dependence of adsorption. And while a variety of materials have been tested for PCR compatibility [11], our study is the first to investigate a wide range of materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jeyachandran et al showed that BSA molecules can be adsorbed to both hydrophobic and hydrophilic surfaces [23] with differing adsorption mechanisms and rates [9]. Prakash et al systematically studied polymerase adsorption on 13 materials [11], but this study did not use actual PCR conditions, and thus the results are not necessarily translatable to PCR compatibility due to the temperature dependence of adsorption. And while a variety of materials have been tested for PCR compatibility [11], our study is the first to investigate a wide range of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al systematically studied polymerase adsorption on 13 materials [11], but this study did not use actual PCR conditions, and thus the results are not necessarily translatable to PCR compatibility due to the temperature dependence of adsorption. And while a variety of materials have been tested for PCR compatibility [11], our study is the first to investigate a wide range of materials. Some solutions that avoid the problem of inhibitory effects of certain materials' in enzymatic reactions, such as PCR, have been reported [21,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofouling often results in increased sample stiction to the surface, exhibited by a significant drop in droplet contact angles that adversely affects sample actuation and device performance. 30 In addition to this, biofouling followed by uncontrolled and unrestricted desorption of proteins becomes a source of cross contamination, which limits device reusability. Researchers have developed intricate strategies to address and overcome the problem of biofoul- ing, most of which are based on superficial modifications of surfaces by depositing self-assembled monolayers or other polymeric materials which respond to optical, thermal, chemical ͑pH͒, or electrical signals to control interfacial interactions.…”
Section: Applicationsmentioning
confidence: 99%